The Influence Of Self-Efficacy, Motivation, And The Mubâsyarah Method On Arabic Language Learning Achievement In SMP Quran Darul Fattah Bandar Lampung - Anggraini, Yuli; Erlina; Muhammad Akmansyah; Sovia Mas Ayu; Koderi; Fachrul Ghazi (An Naba, 2024)
This research is based on psychological and academic problems that arise due to Self-efficacy, low student learning motivation, as well as the learning methods used so that students' Arabic language learning achievement is still low. This design is in accordance with the research objectives, namely to find and analyze the effect of Self-efficacy, learning motivation, and the mubâsyarah method partially and simultaneously or together on Arabic language learning achievement of VII grade in SMP Qur’an Darul Fattah Bandar Lampung. This research is a quantitative study using a survey approach, with a population of 225 students and as for the sample of this study were 54 students. Data were taken using a questionnaire that had been tested for validity and reliability. Data processing uses multiple regression analysis techniques using SPSS 26. This study shows that there is an effect of Self-efficacy, learning motivation, and mubâsyarah method partially on learning achievement. This is obtained based on the SPSS output table, it is known that the simple regression coefficient value of Self-efficacy, learning motivation, and mubâsyarah method on learning achievement is 61.366; 68.236; 66.069 with the variable coefficient of Self-efficacy, learning motivation, and mubâsyarah method is 0.565; 0.306; 0.416. Furthermore, it is known that the significance value is 0.000 <0.05, which can be concluded that Self-efficacy, learning motivation, and the mubâsyarah method simultaneously affect student learning achievement. in the model summary table by looking at R Square = 0.466 so the effect is 46.6% while the rest of student learning achievement is influenced by other factors outside the model studied.